2020
DOI: 10.1002/ecs2.3076
|View full text |Cite
|
Sign up to set email alerts
|

The relative performance of sampling methods for native bees: an empirical test and review of the literature

Abstract: Many bee species are declining globally, but to detect trends and monitor bee assemblages, robust sampling methods are required. Numerous sampling methods are used, but a critical review of their relative effectiveness is lacking. Moreover, evidence suggests the relative effectiveness of sampling methods depends on habitat, yet efficacy in urban areas has yet to be evaluated. This study compared the bee community documented using observational records, targeted netting, mobile gardens, pan traps (blue and yell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
177
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 135 publications
(188 citation statements)
references
References 71 publications
8
177
2
1
Order By: Relevance
“…First, it is possible that at cheatgrass-colonized sites vane traps were more visually apparent due to the relatively homogenous structure of the vegetation and thus more attractive to foraging bees. For example, some authors have suggested that passive traps tend to become increasingly attractive when floral displays are not abundant [ 29 , 32 , 51 ]. Similarly, bees captured in sites with high cheatgrass cover may be responding from nearby patches of foraging habitat or recruited from other distal locations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, it is possible that at cheatgrass-colonized sites vane traps were more visually apparent due to the relatively homogenous structure of the vegetation and thus more attractive to foraging bees. For example, some authors have suggested that passive traps tend to become increasingly attractive when floral displays are not abundant [ 29 , 32 , 51 ]. Similarly, bees captured in sites with high cheatgrass cover may be responding from nearby patches of foraging habitat or recruited from other distal locations.…”
Section: Discussionmentioning
confidence: 99%
“…Traps consisted of an ultra-violet reflective blue vane fixed to a yellow collection bucket (SpringStar, Woodinville, WA, USA). Although previous research suggests that bee sampling method may impact detection of habitat factors influencing bee communities [29], blue vane traps are well suited for collecting across large landscapes as they are easily deployed and are not biased to observer skill or abilities [30][31][32]. Traps were placed at the previously established central location at each site to sample bee assemblages over four separate periods (May, June, July, and August) that corresponded with the assessments of floral cover.…”
Section: Bee Collection Proceduresmentioning
confidence: 99%
“…And yet, supplemental floral resources provided by wildflower strips did not alleviate the negative effect of honey bee hive presence on wild bees in our study, as would be predicted under limited floral resources. However, wild bee populations did not measurably benefit from wildflower strips on farms and we cannot determine the extent to which they were utilized relative to control farm field margins, as trap counts cannot infer foraging behavior 41 , 42 . An additional possible mechanism is that honey bee foraging within an area can reduce wild bee floral visitation 51 ; thus, actively foraging honey bees on farms could have depressed wild bee activity.…”
Section: Discussionmentioning
confidence: 98%
“…For example, areas with relatively robust natural habitat, such as the Eastern Shore of the Mid-Atlantic, U.S., may demonstrate less of an effect from wildflower strips than areas with an intermediate proportion of natural habitat in the landscapes surrounding farms 39 , 40 . Additionally, while necessary in our study due to logistical constraints, pan and blue vane traps often under-sample bees relative to other methods such as netting at flowers or floral visitation observations 41 , 42 . For example, in the U.K., pan traps collected a lower proportion of pollinator populations where floral resources were abundant than where they were scarce due to competing sources of attractive stimuli 43 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, surrounding floral landscape variables may influence the activity-density of bees [ 13 ]. Consequently, it is suggested that researchers employ other methods, such as targeted sweep netting, to sample the bee community as an alternative or addition to pan traps [ 9 , 14 ]. Nonetheless, pan traps have a long history of use to estimate relative abundance and diversity of bees across treatments, landscape types, etc.…”
Section: Introductionmentioning
confidence: 99%